2010
DOI: 10.1371/journal.pone.0012812
|View full text |Cite
|
Sign up to set email alerts
|

A Brassica Exon Array for Whole-Transcript Gene Expression Profiling

Abstract: Affymetrix GeneChip® arrays are used widely to study transcriptional changes in response to developmental and environmental stimuli. GeneChip® arrays comprise multiple 25-mer oligonucleotide probes per gene and retain certain advantages over direct sequencing. For plants, there are several public GeneChip® arrays whose probes are localised primarily in 3′ exons. Plant whole-transcript (WT) GeneChip® arrays are not yet publicly available, although WT resolution is needed to study complex crop genomes such as Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The RT-PCR primers are from Malik et al (2007). The quantitative RT-PCR primers for microarray validation were designed based on oligonucleotide probes from the Affymetrix GeneChip Brassica Exon 1.0ST Array (Malik et al, 2007;Love et al, 2010). The Arabidopsis hda T-DNA insertion lines were genotyped using the PCR primers shown in Supplemental Table 2.…”
Section: Molecular Analysesmentioning
confidence: 99%
“…The RT-PCR primers are from Malik et al (2007). The quantitative RT-PCR primers for microarray validation were designed based on oligonucleotide probes from the Affymetrix GeneChip Brassica Exon 1.0ST Array (Malik et al, 2007;Love et al, 2010). The Arabidopsis hda T-DNA insertion lines were genotyped using the PCR primers shown in Supplemental Table 2.…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Approaches that distinguish between paralogues within the genome, such as the use of high-density oligonucleotide arrays with exonspecific probes or RNAseq, will also increase the accuracy and depth of these analyses in the future (Trick et al, 2009b;Love et al, 2010). …”
Section: Gene Expression Markers Are Highly Heritable But Not Responsmentioning
confidence: 99%
“…Furthermore, extensive genetic and genomic resources for B. rapa have now been assembled. These include a rapid-cycling mapping population developed from highly inbred lines of rapid cycling (IMB211) and yellow sarson (R500) B. rapa (IniguezLuy et al, 2009), more than 2M Brassica GenBank sequences, and a B. rapa genome sequence made available in 2011 alongside other reference Brassica genome and resequencing projects (Multinational Brassica Genome Project; www.brassica.info/resource/sequencing.php), as well as oligonucleotide microarrays (Trick et al, 2009a;Love et al, 2010).…”
mentioning
confidence: 99%
“…This species can accumulate relatively high Ca concentrations in its leaf mesophyll tissues (Rios et al, 2012). Furthermore, B. rapa has a sequenced genome that enables comparative genomic analyses with Arabidopsis and postgenomic resources, including high-density exon-based expression arrays (Love et al, 2010), populations of mutants identified by targeting induced local lesions in genomes (TILLING) (Stephenson et al, 2010;Wang et al, 2012), and mapping lines (Iniguez-Luy et al, 2009). All of these resources were exploited in this study to test the potential of a Brassica-to-Arabidopsis-to-Brassica workflow.…”
Section: Introductionmentioning
confidence: 99%